Social Campaign Design Supporting Recovery from Childhood Emotional Neglect Among Late Adolescents - Gabrielle Ivy Luna Putri; Firmanda Satria (Universitas Multimedia Nusantara, 2026)
Childhood Emotional Neglect (CEN) is a form of adverse childhood experience characterized by the consistent lack of emotional responsiveness from caregivers, which often remains unrecognized yet significantly affects long-term emotional and interpersonal development. In late adolescence, unresolved CEN may manifest as emotional dysregulation, difficulty forming healthy relationships, and impaired social functioning. In the Indonesian context, public awareness of CEN remains limited, and design-based social interventions addressing its interpersonal impacts are still scarce. This study aims to develop a visual communication–based social campaign that supports interpersonal recovery from the negative effects of Childhood Emotional Neglect among late adolescents. A qualitative descriptive approach was employed, utilizing literature review, questionnaires, in-depth interviews, and observational analysis of existing social campaigns. The campaign was developed through a Design Thinking framework and structured using the AISAS communication model (Attention, Interest, Search, Action, Share), emphasizing empathetic storytelling and emotional engagement. The study resulted in a social campaign titled